Impact of COVID-19 on medical waste management and disposal practices in Nigeria. Issue 1 (31st December 2022) - Etim, Mmemek-Abasi; Omole, David O.; Araoye, Oyindamola V.
Abstract: In recent years, Nigeria has experienced increased outbreaks of Monkeypox, Ebola, Lassa fever, and the latest Coronavirus disease (COVID-19) pandemic. As a result of the epidemics, highly infectious materials such as contaminated needles, syringes, soiled bandages, and contagious disposable personal protective equipment are on the rise. This has resulted in vast volumes of medical waste generation in Nigeria. This study employs relevant scientific works of literature in scholarly sites of Web of Science and Scopus, governments, and multilateral organizations regulatory guidelines for COVID-19. This is to conduct a critical analysis of COVID-19ʹs impact on medical waste management and disposal measures in Nigeria during the pandemic. Results show that, with over 143.01% increase in less than a year, Nigeria's daily average COVID-related medical waste increased from 131.24 tons/day in August 2020 to 318.92 tons/day in January 2021, leading to environmental pollution and a high risk of infection among health workers. The paper further highlights the total daily estimates of PPE (facemasks) used during the COVID-19 pandemic as 171, 908, 091. Medical Waste Management (MWM) challenges persist in most developing and least developed nations as the global population and healthcare services rise. As it stands, Nigeria's population is expected to exceed that of the United States by 2050, and with frequent outbreaks of an epidemic, there is a need for an effective MWM plan. Rapid revalidation and appraisal of the Sustainable Development Goals and the Water, Sanitation, and Hygiene (WASH) for health care facilities in most developing countries is required. The inclusion of epidemic and pandemic readiness, natural disasters preparedness, and climate change is critical in the global objectives of the Sustainable Development Goals.